Lipase-produced omega-3 acylglycerols for the fortification and stabilization of extra virgin olive oil using hydroxytyrosyl palmitate - Gunathilake, Tharuka; Akanbi, Taiwo O.; Barrow, Colin J. (Elsevier, 2021)
Pure concentrates of eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids were used to produce monoacylglycerol and diacylglycerol (MDG) oils via enzymatic glycerolysis in a solvent-free system. Immobilized lipase from Candida antarctica B (Novozym 435) was employed for the glycerolysis reaction with up to 90% product formation in one hour. This lipase also favoured diacylglycerol (DAG) over monoacylglycerol (MAG) production. Products were purified using silica gel chromatography and characterised by capillary chromatography with flame ionization detection (Iatroscan-FID). Purified products were added to extra virgin olive oil (EVOO) at a concentration of 20% w/w. The fortified olive oil was stabilized using hydroxytyrosyl palmitate, an antioxidant prepared by conjugating hydroxytyrosol with palmitic acid using Novozym 435 lipase. In vitro hydrolysis of the fortified oil was also carried out using porcine pancreatic lipase to investigate the mechanism of action of this enzyme on the oil mixtures.